Directions and prospects of digital transformation of public management systems of territorial development in Ukraine - Potravka, L.O.; Zamkovyi, V.M. («Академик Е.А. Бөкетов атындағы Карағанды университеті» КЕАҚ баспасы, 2020)
It is established that the digitalization of all spheres of life is becoming the norm of development of all countries. It was found that the development of the digital economy raises many issues of state regional policy in Ukraine. The analysis of problems of regulation of process of development of digital economy is carried out. The directions and prospects of digital transformation of the system of public management of territorial development in Ukraine are investigated.
Keywords: digital transformation; concept; territorial development; digital economy; smart region